Functional and morphological evolution of remnant pancreas after resection for pancreatic adenocarcinoma. Issue 28 (July 2017) - Park, Shin-Young; Park, Keun-Myoung; Shin, Woo Young; Choe, Yun-Mee; Hur, Yoon-Seok; Lee, Keon-Young; Ahn, Seung-Ik
Abstract : Abstract: Functional and morphological evolution of remnant pancreas after resection for pancreatic adenocarcinoma is investigated. The medical records of 45 patients who had undergone radical resection for pancreatic adenocarcinoma from March 2010 to September 2013 were reviewed retrospectively. There were 34 patients in the pancreaticoduodenectomy (PD) group and 10 patients in the distal pancreatectomy (DP) group. One patient received total pancreatectomy. The endocrine function was measured using the glucose tolerance index (GTI), which was derived by dividing daily maximum serum glucose fluctuation by daily minimum glucose. Remnant pancreas volume (RPV) was estimated by considering pancreas body and tail as a column, and head as an ellipsoid, respectively. The pancreatic atrophic index (PAI) was defined as the ratio of pancreatic duct width to total pancreas width. Representative indices of each patient were compared before and after resection up to 2 years postoperatively. The area under receiver operating characteristic curve of GTI for diagnosing DM was 0.823 (95% confidence interval, 0.699–0.948, P  < .001). Overall, GTI increased on postoperative day 1 (POD#1, mean ± standard deviation, 1.79 ± 1.40 vs preoperative, 1.02 ± 1.41; P  = .001), and then decreased by day 7 (0.89 ± 1.16 vs POD#1, P  < .001). In the PD group, the GTI on POD#14 became lower than preoperative (0.51 ± 0.38 vs 0.96 ± 1.37; P  = .03). PAI in the PD group was significantly lower at 1 month postoperatively (0.22 ± 0.12 vs preoperative, 0.38 ± 0.18; P  < .001). In the PD group, RPV was significantly lower at 1 month postoperatively (25.3 ± 18.3 cm 3 vs preoperative, 32.4 ± 20.1 cm 3 ; P  = .02), due to the resolution of pancreatic duct dilatation. RPV of the DP group showed no significant change. GTI was negatively related to RPV preoperatively ( r  = –0.317, P  = .04), but this correlation disappeared postoperatively ( r  = –0.044, P  = .62). Pancreatic endocrine functional deterioration in pancreatic adenocarcinoma patients may in part be due to pancreatic duct obstruction and dilatation caused by the tumor. After resection, this proportion of endocrine insufficiency is corrected.